The Implementing Of Green Recruitment And Green Training For Managing Turnover Intention - April Gunawan Malau; Widianti Lestari; Derma Watty Sihombing; Rosna Yuherlina Siahaan; Saidal Siburian; Nandan Limakrisna (Dinasti International Journal of Education Management And Social Science, 2024)
The aim of this study is to examine the effect and analysis of the relationship between Green Human Resource Management (GHRM) practices, like Green Recruitment and Green Training, on Turnover Intention. The data set used in this research consists of 90 respondents selected from employees belonging to the Millennial generation at one State-Owned Enterprise, i.e., PT XYZ, Ngurah Rai Bali Airport branch. Also, in this study, Structural Equation Model (SEM) has been used as an analytical tool using Partial Least Squares (PLS). The results showed that: (1) there is a negative impact between Green Recruitment on turnover intention, and (2) there is a negative impact between Green Training on Turnover Intention